2015
DOI: 10.1007/s00405-015-3703-9
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin 1 (Cav-1) and actin-related protein 2/3 complex, subunit 1B (ARPC1B) expressions as prognostic indicators for oral squamous cell carcinoma (OSCC)

Abstract: Caveolin-1 (Cav-1) and Actin-Related Protein 2/3 Complex, Subunit 1B (ARPC1B) have been implicated in various human cancers, yet its role in tumorigenesis remains controversial. Therefore, this study aims to determine the protein expression of these two genes in oral squamous cell carcinomas (OSCCs) and to evaluate the clinical and prognostic impact of these genes in OSCC. Protein expressions of these two genes were determined by immunohistochemistry technique. The association between Cav-1 and ARPC1B with cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
0
19
0
3
Order By: Relevance
“…Previous results have demonstrated that Cav-1 is a growth-inhibitory protein that may act as a tumor suppressor (8,9). Cav-1 expression is downregulated in some forms of cancer, including mesenchymal tumors and sarcomas (8,10); however, in other cancer types; for example, oral squamous cell carcinoma, Cav-1 expression is high (11,12). These findings suggest that Cav-1 has multiple actions in human cancer cells.…”
Section: Introductionmentioning
confidence: 56%
“…Previous results have demonstrated that Cav-1 is a growth-inhibitory protein that may act as a tumor suppressor (8,9). Cav-1 expression is downregulated in some forms of cancer, including mesenchymal tumors and sarcomas (8,10); however, in other cancer types; for example, oral squamous cell carcinoma, Cav-1 expression is high (11,12). These findings suggest that Cav-1 has multiple actions in human cancer cells.…”
Section: Introductionmentioning
confidence: 56%
“…The isoforms they encode have 68% amino acid sequence identity15 and both have six WD40 domain repeats predicted to form a β-propeller-fold316. ARPC1A has been implicated as a regulator of cell migration and invasion in pancreatic cancer14, while increased ARPC1B has been linked to oral squamous cell carcinoma17. Independent of its function in Arp2/3, ARPC1B has also been identified as a centrosomal protein involved in mitosis1819.…”
mentioning
confidence: 99%
“…Dos estudos com baixo risco de viés, nenhum respondeu a todas as questões do MAStARI, isto é, 11 deles (Tsai et al, 2008;Liu et al, 2010;Bose et al, 2012;Klimowicz et al, 2012;Coutinho-Camillo et al, 2013;Grimm et al, 2013;Lee et al, 2014;Magnussen et al, 2014;Auzair et al, 2016;Fernández-Valle et al, 2016;Gissi et al, 2016) responderam de forma positiva a maioria das questões da avaliação qualitativa, ou seja, não responderam a uma única questão, e obtiveram o índice de 90,9% na escala do risco de viés. As questões não respondidas foram a 3 ou 7, isto é, fatores de confusão e motivos pela perda de seguimento.…”
Section: Discussionunclassified
“…A expressão imuno-histoquímica do Cav-1 e ARPC1B no carcinoma epidermoide oral foi avaliada quanto ao impacto no prognóstico da doença (Auzair et al, 2016). Os autores observaram que o Cav-1 e ARPC1B foram encontrados significativamente mais expressos no carcinoma epidermoide do que na mucosa oral normal.…”
Section: Discussionunclassified
See 1 more Smart Citation